Benzenecarboxylic acid production by oxidation of Shenmu char powders with aqueous sodium hypochlorite. (15th October 2020) - Lv, Jing-Hui; Wei, Xian-Yong; Zhang, Yang-Yang; Zong, Zhi-Min; Zhang, Yu-Long; Ma, Ming-Jie; Bai, Hong-Cun
Graphical abstract: Highlights: Arenecarboxylic acids were produced in high yields by oxidizing SCPs with ASHC. The CAR structures in CPs suppress the formation of chlorine-substituted compounds. O2 − plays a crucial role in oxidizing ARs in SCPs to arenecarboxylic acids. Conjugation effect and electron-withdrawing effect affect the product distribution. Abstract: Char powders (CPs) are a promising feedstock for producing benzenecarboxylic acids (BCAs) due to their abundant condensed aromatic rings. An innovative exploration on the related mechanisms for oxidation and chlorination was attempted to guide the production of target BCAs in higher yields. The results declare that Shenmu CPs were converted to valuable BCAs in the yield of 16.2%. According to the product distribution, the total relative content (4.3%) of chlorine-substituted alkanoic acids (CSAAs) is much higher than that (0.2%) of alkanoic acids, while the result of chlorine-substituted BCAs is just the opposite and no chlorine-substituted arenecarboxylic acids with multiple aromatic rings (ARs) were produced. All the CSAAs have only short-chains. Carboxylic groups (CGs) tend to be chlorinated, but the steric effect of benzene ring leads to the inertness of most BCAs towards chlorination. The conjugation effect between CGs and ARs facilitates degrading condensed aromatics by stabilizing aryl radical intermediates. Thereby, the activity towards chlorination decreases with increasing the number of CGs, condensation degree, and carbon numbers in the aliphatic chains.